BCT582: Research methodology / College of Built Environment - UiTM, College of Built Environment (Universiti Teknologi MARA (UiTM), 2020)
This course will provide an understanding of the research process, and the theory and methods used in the collection and analysis of data. The topics include issues to consider when choosing research subjects, indentifying research problems, problems formulation, preparin the research proposal, literature review, research methodology, research design, construct questionnaires, conducting surveys and production of the dissertation. The research methodology elaborates on data collection and various data analysis and interpretation techniques including statistical or non-statistical data analysis techniques.